Nusantarazation Environmental Paradigm: Sustaining Biodiversity and Culture in Nusantara Malay Archipelago with Local Ecological Knowledge (LEK) - Sazlina Salleh; Mahadi Mohammad; Mohammad Reevany Bustami (Dwijendra University, 2021)
Since Nusantara Malay Archipelago is a maritime community, its indigenous knowledge and local wisdom is largely connected to sea life and water. Nevertheless, there are also mountains, valleys, forests and flatlands; hence, local knowledge is also connected to these landscapes and spaces. This article submits the environmental paradigm of Nusantarazation and its interconnectedness with local ecological knowledge (LEK) as well as reports on findings in the form of case exemplars in the field related to these constructs. The authors argue that Nusantarazation is an epistemological paradigm which is able to decolonize environment knowledge and provide an integrative framework for LEK, sustainable practices and technological know-how. The spatial scope covers mainly areas in Malaysia and Indonesia as these are part of Nusantara. Among the key findings are that LEK tend to be accompanied with seemingly unscientific or mythical narratives but are translated into practices that promote sustainability either in the land or waters. This article also capture various local constructs and beliefs that capture the underlying value systems which are integral to conservation and ecological balance. Nevertheless, the Nusantarazation environmental paradigm encounters challenges from colonial legacies of power modern practices and industrial complex that threaten to harm the environment and humanity.